Discussion on New Ideas of Technical Consultation Service in the Whole Process of Implementation Stage of Reservoir Resettlement - ZHANG Jiahao; XU Lin; DU Yong; YAN Tiemei; GUAN Shifeng (Renmin Zhujiang)
Under the background of high-quality development of water conservancy in the new era,there are many problems in the implementation stage of reservoir resettlement in China,such as the disunity of procedure standards,the lack of work content refinement,many major changes in the implementation process,and insufficient experience of the implementation subject.The reservoir resettlement work adopts the management system of government leadership,hierarchical responsibility,a county as a unit,and the project’s legal person participation.The design unit,project owner,and other technical units have low participation in the resettlement implementation,and there is a lack of rules and regulations to restrain them.The local government has many difficulties in reservoir resettlement implementation,such as the shortage of engineering technicians,the lack of project management experience,and the uncertainty of resettlement policies.In addition,the complexity of resettlement in the implementation stage makes it difficult to achieve many control objectives such as the progress,investment,and quality of the reservoir resettlement implementation.Through a systematic analysis of the difficulties and problems in the stage,this paper takes the lead in proposing the working method of carrying out technical consultation service in the whole process of the implementation stage of reservoir resettlement,creatively analyzes the relevant work content,and puts forward suggestions for addressing the difficulties of the county government in the implementation stage of reservoir resettlement.